2022
DOI: 10.3390/su142215368
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study on Health Risk Assessment of Exposure to PM2.5-Bound Toxic Metals in the Industrial Metropolitan of Rayong, Thailand

Abstract: The concentrations of PM2.5 and metallic elements were measured in Rayong during the dry season (November 2021 to April 2022). The mean PM2.5 concentration was 20.1 ± 10.9 µg/m3 (4.9–52.3 µg/m3). Moreover, the percentages of days when those PM2.5 concentrations exceeded the daily WHO and US-EPA NAAQS limit were 56.8% and 10.2%, respectively. However, the levels did not exceed 50 µg/m3, which is the limit of the 24 h standard defined by the PCD in Thailand. The dominant heavy metals and elements in PM2.5 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The sampling sites were selected in Ahvaz city, located at 31.3183° N, 48.6706° E longitude and latitude, respectively with elevation of 12 m above the sea level in southwest of Iran. Ahvaz, with a population of around 1.5 million, is recognized as one of the seven major cities in Iran.…”
Section: Study Area and Sampling Stationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling sites were selected in Ahvaz city, located at 31.3183° N, 48.6706° E longitude and latitude, respectively with elevation of 12 m above the sea level in southwest of Iran. Ahvaz, with a population of around 1.5 million, is recognized as one of the seven major cities in Iran.…”
Section: Study Area and Sampling Stationmentioning
confidence: 99%
“…Also, according to the age groups, the highest risk of carcinogenesis was calculated for adults > children > infants respectively. Kawichai et al Rayong, Thailand showed that the carcinogenic risk of chromium for adults and children was higher than 10 -4 , for infants between 10 -4 and 10 -6 , and the www.nature.com/scientificreports/ carcinogenicity of other metals was within the safe range 48 . In addition to the earth's crust, human activities can also increase the concentration of Cr in breathing air.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Anthropogenic sources are more likely to be associated with fine particles, while natural sources like soils or crustaceans that contain metal elements are more likely to be associated with coarse particles [ 27 ]. In numerous studies of PM 2.5 -bound elements, the lifetime cancer risk (CR) and hazard quotient (HQ) models revealed increased morbidity and mortality from lung cancer and non-carcinogenic risks [ 28 ]. Metals like Pb, Cu, Ni, and Fe that can cause respiratory and cardiovascular diseases were found in PM 2.5 samples in a recent study carried out in high-traffic areas of Karachi and Kashmore, Sindh [ 29 ].…”
Section: Introductionmentioning
confidence: 99%